Manifiesto al Estado, de la Diputación Permanente unida con el Consejo de Gobierno y diputados residentes en la capital : Coahuiltexanos: El Poder Legislative del Estado representado hoy legalmente por the reunión . ([publisher not identified], 1834)
Broadside decrying the state of the Federal government and its relation with the states.